Techno-Sociopreneurship Tourism Industry: Model Pengelolaan Daerah Tertinggal Menuju Daerah Maju dan Berdaya Saing - Muhammad Fajar Wahyudi Rahman; Firza Oktavia Nurul Kumala (Inspirasi Nusantara, 2021)
Based on data from the Village Community Empowerment Service East Java, Indonesia the districts/cities that still have underdeveloped villages include Lamongan Regency, which is recorded at most, namely 42 villages. From the semi-systematic literature review, three papers were selected as references in an example of a development model for an area. The author's recommendation as a role model for the management of underdeveloped areas is a combination of: community-based tourism approaches, website-based fundraising called